Anishinaabe Learning Places: Teaching and Learning through Gift, Relational, Movement and Spirit Pedagogies - Hupfield, John Robert (2023)
Powwows have always been a place of dynamic colours, beadwork, a celebration of life on the land, a site for Anishinaabeg to ‘dance, sing, and pray, the Anishinaabe way.’ Anishinaabe pedagogy and powwow as place: Teaching and Learning through Gift, Relational, Movement and Spirit Pedagogies is a project that examines the ways in which powwow as place can provide spaces for teaching and learning within powwow families. As a grass dancer themselves, the author centres relationship with three other powwow families through a methodology rooted in Anishinaabewin (Indigenous knowledge systems), dibaajimowinan (storysharing), and nbwaachewin (visiting). Through a series of ZOOM sessions, stories were shared and knowledge co-constructed about Anishinaabe pedagogy through processes of reciprocity and relationality. The stories shared by families were oft-framed by colonization, naming its impacts on family structures and Anishinaabe identity - the dismantling of kinship systems. Powwow as place was described as a space that not only provides respite from ongoing forms of colonization, but fosters kin-making, wholistic wellbeing, and the learning of Anishinaabewin through coming to understand teachings about kinship through roles and responsibilities. Powwow families expressed the need to nurture the ‘spirit’ of the learner, a notion rooted in wholism that they felt is oft-lacking in zhaagnosh (non-Anishinaabe) learning settings. These findings indicate a need for powwows to be reframed from cultural gatherings and celebrations, to critical places of learning/teaching for Anishinaabeg. The focus on gifts of learners, reframing relationships between teacher and learner relationships, and a call for the hosting of more Anishinaabeg places of learning such as powwow, are all aspects that non-Indigenous educational contexts can learn from.